Selective Serotonin Reuptake Inhibitors: A Review of its Effects on Intraocular Pressure - Costagliola, Ciro; Parmeggiani, Francesco; Semeraro, Francesco; Sebastiani, Adolfo (Current Neuropharmacology, 2008)
The increase in serotonin (5-HT) neurotransmission is considered to be one of the most efficacious medical approach to depression and its related disorders. The selective serotonin reuptake inhibitors (SSRIs) represent the most widely antidepressive drugs utilized in the medical treatment of depressed patients. Currently available SSRIs include fluoxetine, sertraline, paroxetine, fluvoxamine, citalopram and escitalopram. The primary SSRIs pharmacological action's mechanism consists in the presynaptic inhibition on the serotonin reuptake, with an increased availability of this amine into the synaptic cleft. Serotonin produces its effects as a consequence of interactions with appropriate receptors. Seven distinct families of 5-HT receptors have been identified (5-HT1 to 5-HT7), and subpopulations have been described for several of these. The interaction between serotonin and post-synaptic receptors mediates a wide range of functions. The SSRIs have a very favorable safety profile, although clinical signs of several unexpected pathologic events are often misdiagnosed, in particular, those regarding the eye. In all cases reported in the literature the angle-closure glaucoma represents the most important SSRIs-related ocular adverse event. Thus, it is not quite hazardous to hypothesize that also the other reported and unspecified visual disturbances could be attributed - at least in some cases - to IOP modifications. The knowledge of SSRIs individual tolerability, angle-closure predisposition and critical IOP could be important goals able to avoid further and more dangerous ocular side effects.
Keywords: side effects